The Effects of Folktale Telling with Role-Playing Activities on Social Awareness of Young Children - Khaopongsai , Umaporn; Samahito, Chalatip (Interdisciplinary Academic and Research Journal, 2023)
Organizing folktale-telling and role-playing activities is one of the educational activities that allow children to experience places and people. Folktale stories can help foster social awareness in children because the character traits of storytellers can help children develop empathetic behavior and feelings. The object of this study was to study the effects of folktales telling with role-playing activities on social awareness of early children. The samples were 21 male and female children 3-4 years old studying in K1, semester 2, the academic year of 2022, Tantawan demonstration preschool, Muban Chombueng Rajabhat University under the Ministry of Higher Education, Science, Research and Innovation. The study instruments included 24 plans of folktales telling and roleplaying activities, a form of social awareness behavioral of early childhood children, and journals. Data were analyzed by mean, standard deviation, and content analysis. The results showed that young children who received folktale-telling and role-playing activities had higher average scores of social awareness than before participating in folktale-telling and role-playing activities. In addition, they had higher average scores in the aspects of empathy than the respectful.